2023
DOI: 10.3389/fimmu.2023.1019445
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of eight RNA-modified regulators correlating with immune infiltrates during the progression of osteoarthritis

Abstract: BackgroundRNA modifications in eukaryotic cells have emerged as an exciting but under-explored area in recent years and are considered to be associated with many human diseases. While several studies have been published relating to m6A in osteoarthritis (OA), we only have limited knowledge of other kinds of RNA modifications. Our study investigated eight RNA modifiers’ specific roles in OA including A-to-I, APA, m5C, m6A, m7G, mcm5s2U, Nm and Ψ together with their relationship with immune infiltration.MethodsR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“… 55 Although predictive models have been widely used, their application in early diagnosis and determining immune/inflammatory cell infiltration in OA remains limited. 10 , 57 Therefore, effective predictive strategies for distinguishing various inflammatory stages and for early diagnosis of OA should be developed. In this study, two disulfidptosis-related subtypes of OA were identified via consensus clustering.…”
Section: Discussionmentioning
confidence: 99%
“… 55 Although predictive models have been widely used, their application in early diagnosis and determining immune/inflammatory cell infiltration in OA remains limited. 10 , 57 Therefore, effective predictive strategies for distinguishing various inflammatory stages and for early diagnosis of OA should be developed. In this study, two disulfidptosis-related subtypes of OA were identified via consensus clustering.…”
Section: Discussionmentioning
confidence: 99%